2022
DOI: 10.1021/acs.inorgchem.2c00501
|View full text |Cite
|
Sign up to set email alerts
|

Rigidified Derivative of the Non-macrocyclic Ligand H4OCTAPA for Stable Lanthanide(III) Complexation

Abstract: The stability constants of lanthanide complexes with the potentially octadentate ligand CHX OCTAPA 4– , which contains a rigid 1,2-diaminocyclohexane scaffold functionalized with two acetate and two picolinate pendant arms, reveal the formation of stable complexes [log K LaL = 17.82(1) and log K YbL = 19.65(1)]. Luminescence studies on the Eu 3+ and Tb 3+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 128 publications
(287 reference statements)
5
18
0
Order By: Relevance
“…Eu( iii ) emission spectra recorded in the 5.4–11.3 pH range confirm the presence of a single Eu–containing species. The stability constant obtained for EuL is comparable to those of other Ln( iii ) complexes with similar acyclic ligands containing picolinate chelating groups, 55 with the formation of an octadentate complex. According to this model, at physiological pH = 7.4 and 1 : 1 Eu : L molar ratio, the ML species is largely prevalent (∼100%) and, in the perspective of in vitro application experiments, the stability looks suitable, as it is close to that of macrocyclic ligands already employed in molecular imaging applications ( e.g.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Eu( iii ) emission spectra recorded in the 5.4–11.3 pH range confirm the presence of a single Eu–containing species. The stability constant obtained for EuL is comparable to those of other Ln( iii ) complexes with similar acyclic ligands containing picolinate chelating groups, 55 with the formation of an octadentate complex. According to this model, at physiological pH = 7.4 and 1 : 1 Eu : L molar ratio, the ML species is largely prevalent (∼100%) and, in the perspective of in vitro application experiments, the stability looks suitable, as it is close to that of macrocyclic ligands already employed in molecular imaging applications ( e.g.…”
Section: Resultssupporting
confidence: 61%
“…The protonation constants for ligand L were obtained from the best fit of pH data and are reported in Table 1, along with those relative to other ligands previously studied by some of us 12,46 or others 54,55 (Fig. 3) for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…This has been observed previously very often when investigating the relaxation properties of Gd(III) complexes. 89,92,93 Values of E v close to 1 kJ mol −1 were reported for the lanthanide aqua ions. 3 The values of τ R obtained from the fits of the data are very reasonable, considering the size of the complexes, 94 with the slightly longer value of τ R being observed for the complex with the highest molecular weight.…”
Section: Afmentioning
confidence: 77%
“…Thus, complexes with H 4 CHX OCTAPA showed similar thermodynamic stability but are less prone to dissociation. 29,30 Lanthanide H 4 CHX OCTAPA complexes were also studied 31 and radiolabelling studies with 225 Ac were reported. 25 Herein, we expand the family of rigid H 4 OCTAPA derivatives and assess their potential for developing Bi( iii )-based radiopharmaceuticals.…”
mentioning
confidence: 99%
“…This suggests that the [Bi( CHX OCTAPA)] − and [Bi( Cp OCTAPA)] − complexes display a cis -( S , R ) conformation, as observed for the small sized lanthanide ions. 31…”
mentioning
confidence: 99%